Estrategia didáctica LERNEN ZU SPRECHEN en el desarrollo de la producción oral del idioma alemán de los estudiantes de la escuela académico profesional de idiomas de la UNSM -T - 2012-II - Bruno Huachez, Dany Deibi (2012)
When we talk about the teaching of the language skills in general (listening, speaking, reading and writing), different conflicts appear that can retard or prevent the German language student to be able to be competent in the use of these skills in an appropriate form. The oral production, one of the most immediate skills that the student needs to possess, is attributed an endless number of factors that allow or avoid its development. This research deals with a methodological proposal for the German language searching. Having in mind, the challenge presented by the diversity of students in the classrooms, it is necessary to develop strategies that are feasible of using, so that this allows and provides answers to the student's needs. This research has a constructivist approach to achieve a meaningful learning in student, in order to develop the oral production in the German language. The proposal showed here is based on the creation of the didactic strategy LERNEN ZU SPRECHEN" for oral production development of the German language of the Academic Language School Students of the UNSM-T - 2012-II. This strategy was oriented to improve the students' oral production in the components: fluency, coherence, pronunciation and grammar. The data gathering was carried out in the Academic Language School, Faculty of Education and Humanities of the National University of San Martin, thus obtaining a sampling population of 24 students. In order to measure the students' oral production, a pre and post-test were applied at the beginning and at the end of the eight learning sessions, each test was made up of 50 items divided into the four components. Through this study, it has been proved that through the application of oral activities which include learning strategies and a comfortable working environment, the oral production of German students have improved considerably.